PREVALENCE AND RISK FACTORS OF ASYMPTOMATIC CEREBRAL INFARCTION - R. R. Zhetishev; P. R. Kamchatnov; N. A. Mikhailova; A. R. Ivashchenko (Klinicist)
Acute stroke manifesting as focal neurological deficit is a leading cause of death and disability. Of interest is the problem of asymptomatic cerebral infarctions (AСI), in which there is focal medullary involvement unaccompanied by the development of focal symptoms. The role of AСI as a marker for the progression of vascular dementia and for the further development of symptomatic stroke has not been adequately explored. There are current instrumental (neuroimaging) criteria for diagnosing AСI. An update on the risk factors of AСI and their association with the further course of cerebrovascular involvement is analyzed. The results of a number of prospective studies conducted in the countries of Asia and Europe to investigate risk factors for AСI and their prognostic value are considered in detail. There is a relationship between hypertension, blood pressure instability, type 2 diabetes mellitus, some other factors, and a significantly increased risk for AСI. Based on the results of analyzing the data available in the literature, the authors demonstrate the association of prior AСI with the higher rates of progressive vascular cognitive impairments. A correlation is shown between prior AСI and an increased risk for further development of ischemic stroke accompanied by its clinical symptoms, which leads to disability. It is suggested that it is advisable to implement measures for secondary cardiovascular disease prevention, including the administration of antiaggregatory and antihypertensive agents, in patients with AСI.